Biophysical model to predict lung delivery from a dual bronchodilator dry-powder inhaler - Myrna B. Dolovich; Andreas Kuttler; Thomas J. Dimke; Omar S. Usmani (Elsevier, 2019)
A biophysical lung model was designed to predict inhaled drug deposition in patients with obstructive airway disease, and quantitatively investigate sources of deposition variability. Different mouth-throat anatomies at varying simulated inhalation flows were used to calculate the lung dose of indacaterol/glycopyrronium [IND/GLY] 110/50 µg (QVA149) from the dry-powder inhaler Breezhaler®. Sources of variability in lung dose were studied using computational fluid dynamics, supported by aerosol particle sizing measurements, particle image velocimetry and computed tomography. Anatomical differences in mouth-throat geometries were identified as a major source of inter-subject variability in lung deposition. Lung dose was similar across inhalation flows of 30-120 L/min with a slight drop in calculated delivery at high inspiratory flows. Delivery was relatively unaffected by inhaler inclination angle. The delivered lung dose of the fixed-dose combination IND/GLY matched well with corresponding monotherapy doses. This biophysical model indicates low extra-thoracic drug loss and consistent lung delivery of IND/GLY, independent of inhalation flows. This is an important finding for patients across various ages and lung disease severities. The model provides a quantitative, mechanistic simulation of inhaled therapies that could provide a test system for estimating drug delivery to the lung and complement traditional clinical studies. Keywords: Inhaler devices, Lung deposition, Computational fluid dynamics, Chronic obstructive pulmonary disease, Dry powder inhaler